Ultrasonic-time-domain-reflectometry as a real time non-destructive visualisation technique of concentration polarisation and fouling on reverse osmosis membranes - Koen, Louis Johannes (Stellenbosch : Stellenbosch University, 2015)
Thesis (MIng)--University of Stellenbosch, 2000.